2020
DOI: 10.1136/openhrt-2019-001152
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance T2* mapping for the assessment of cardiovascular events in hypertrophic cardiomyopathy

Abstract: BackgroundHypertrophic cardiomyopathy (HCM) is associated with an increased risk of adverse cardiac events. Beyond classic risk factors, relative myocardial ischaemia and succeeding myocardial alterations, which can be detected using either contrast agents or parametric mapping in cardiovascular magnetic resonance (CMR) imaging, have shown an impact on outcome in HCM. CMR may help to risk stratify using parametric T2* mapping. Therefore, the aim of the present study was to evaluate the association of T2* value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
(60 reference statements)
0
6
0
1
Order By: Relevance
“…In HCM patients, the values are reduced, reflecting areas of reduced perfusion, and correlate with T1 mapping, showing a temporal association between fibrosis and silent ischemia [ 2 ]. Similar to the presence of LGE, abnormalities with T2* values were also associated with ventricular arrhythmias [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…In HCM patients, the values are reduced, reflecting areas of reduced perfusion, and correlate with T1 mapping, showing a temporal association between fibrosis and silent ischemia [ 2 ]. Similar to the presence of LGE, abnormalities with T2* values were also associated with ventricular arrhythmias [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Especially in non-obstructive HCM patients, it was observed that low T2* values are minimally associated with arrhythmic events. There was no association between T2* with heart failure, thus myocardial fibrosis by LGE remains the strongest predictor, and T2* mapping may be used only in certain clinical contexts [89].…”
Section: Cardiac Magnetic Resonancementioning
confidence: 92%
“…To determine statistical associations between the different parameters, Pearson correlation for normally distributed or Spearman correlation analysis for not-normally distributed data was performed. In the end, receiver operating characteristics were used to generate cut-off values to identify more pronounced elevated pericardial values above the third quartile 16. A p value less than 0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%